Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - You, Ya; Yang, Wei-Guo; Zhang, Shun; Su, Ming-Li; Peng, Qi-Lin; Zhao, Wan-Jiang; Yuan, Ruo; Xu, Shang-Cheng; Liang, Wen-Bin (Analytica chimica acta, 2025)
As global food production continues to surge, the widespread use of herbicides has also increased concurrently, posing challenges like health risks and environmental pollution. Traditional detection methods for pesticide residues, such as diquat (DQ), were hampered by limitations like high expenses, lengthy detection times and complex operations, restricting their practical application in rapid clinical diagnosis. In light of the pressing necessity for the identification of minute pesticide residues and the intrinsic constraints of small molecule analysis, a novel chromophotometric biosensor targeting small molecules was developed based on bi-epitopes on single antibody to immobilize two DQ-PAL, inhibiting the hybridization of DQ-PAL. Accordingly, the free DQ-PAL could hybridize with each other to form a G-quadruplex for a highly selective analysis of DQ with a detection limit of 26.3 pg/mL and 10 pg/mL by chromophotometric and image colorimetric method respectively. Furthermore, this designed biosensor has been successfully applied to evaluate the levels of DQ residues in real samples, providing an efficient solution for the biological analysis of small molecule targets and enhancing food safety concerning pesticide residues. In comparison to conventional techniques, this biosensor has the advantages of user-friendly operations, portability, high sensitivity, low detection limit and minimal background interference, making it well-suited for clinical diagnostics. At the same time, this technology provides a new idea for the rapid in vitro detection of biological small molecules, and shows great potential applications in agricultural residue-related food safety. [Display omitted] •Antibody competitive recognition strategies enable small molecule detection.•A distance-regulated G-quadruplex/heme-mediated TMB-H2O2 chromogenic system is used for small molecule quantification.•The method permits the efficient and straightforward visualization of pesticide small molecules in the absence of labelling.